Blockchain Accounting for Transparency, Accountability, and Audit Practice: A Systematic Literature Review - Wilda Anabia Prasasti; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (International Journal of Applied Business and International Management, 2025)
Blockchain has become a game-changing accounting technology that is changing how businesses document, validate, and report financial data. This study aims to examine the effect of blockchain on accounting, auditing, and financial reporting’s transparency and accountability by conducting a systematic literature review (SLR) of recent works (2023–2025). Drawing on 39 peer-reviewed articles from the Scopus database that as outlined in the PRISMA process, this review synthesizes key issues, research gaps, and directions of future research. Findings demonstrate that blockchain improves efficiency, security, fraud prevention, and data transparency, but adoption remains constrained by regulatory ambiguity, infrastructural limitations, and organizational resistance. Research gaps remain in developing economies, in adoption by accounting professionals, and in the integration of blockchain with accounting standards. Future research is suggested to address these challenges by combining socio-technical and institutional perspectives. The study significantly advances the understanding of scholars, practitioners, and policymakers of how to successfully and sustainably integrate blockchain technology into accounting systems.